An experimental study on the radar absorbing characteristics of folded core structures. (15th June 2018) - Wang, Zhijin; Zhou, Chen; Khaliulin, Valentin; Shabalov, Alexey
Abstract: Folded core sandwich structures are promising multifunctional structures for both load bearing and radar absorbing capability. This paper presents an experimental study on the radar absorbing characteristics of folded core structures. The influences of various factors on the folded core radar cross section (RCS) are investigated. The experiments were carried out in an anechoic chamber. Comparisons are made between folded core samples and an aluminium flat panel. The results show that the folded core height has significant effects on the radar absorbing performance of V-pattern folded core, while core material only leads to a slight difference. The RCS of V-pattern folded core is lower than that of the flat panel, while the RCS of M-pattern folded core is of the same order of magnitude as that of the flat panel with a much wider range.